Management of Breast Cancer during COVID-19 Pandemic: Trends of the Intervals to Radiotherapy in a Single Center Cohort - Jacopo Di Muzio; Valeria Chiofalo; Cristiano Grossi; Francesco Olivero; Simona La Sala; Anna Mussano; Umberto Ricardi (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: COVID-19 pandemic led to a drastical rearrangement within healthcare staff and facilities. Due to its high incidence, management of breast cancer (BC) was particularly critical during the COVID-19 pandemic, and the reduction of healthcare staff and facilities influenced the timing in BC care. The aim of the present report was to analyze the timing from diagnosis to surgery, from diagnosis to radiotherapy (RT) start and from surgery to RT start during the COVID-19 pandemic. Methods: We retrospectively collected data of women with BC treated with Radiotherapy (RT) after surgery at our Institution (Department of Oncology, Radiation Oncology, S. Anna Hospital, Turin, Italy), during the COVID-19 pandemic. To evaluate patients’ data according to the different stages of the pandemic, we identified 4 periods: first wave (FW), first reopening (FR), second wave (SW) and second reopening (SR). Among the 4 periods, we divided patients in 2 groups: patients who underwent adjuvant chemotherapy (CT) before RT (CT-group), and those who received exclusive adjuvant RT (non-CT group). Results: from early March 2020 to 31 March 2022, 464 patients were treated. After patients’ selection, data from 390 patients were analyzed. Overall, the average interval between biopsy and RT in the non-CT group was 202 days during the FW (101–386), 172 days (85–242) during the FR, 136 days (69–366) during the SW, 159 days (77–455) during the SR. In the CT group, the average interval from biopsy to RT start was 337 days (224–495) during the FW, 277 days (209–496) during FR, 297 days (220–419) during the SW, and 261 days (169–447) during the SR. Conclusions: we reported our experience during these two years of the pandemic and how COVID-19 impacted the timing of the management of patients with BC. Overall, during the viral waves there was a remarkable increase in the interval between biopsy/surgery and RT. Nonetheless, we managed to keep optimal BC care and favorable interval trends were observed with reopening phases.